306 Human biomonitoring for emergency responders – experience, benefits and limitations –. (24th April 2018) - Bader, M; Bäcker, S; Jäger, T; Van Bortel, G; van Weyenbergh, T; Verwerft, E; Webendörfer, S; Oberlinner, C; Lang, S
Abstract : Introduction: Human Biomonitoring (HBM) was introduced decades ago for the monitoring of workers' exposure to chemicals. Meanwhile, procedures like sample collection/transport are standardised and assessment values are continuously derived or updated. But HBM is also a useful tool for monitoring exposure after incidents such as chemical spills or large fires. Accordingly, the exposure situation of firefighters, other emergency responders or bystanders has come into the focus of occupational and environmental medicine and toxicology. Methods: A standardised and streamlined procedure for the HBM of emergency responders was established at two large chemical production sites. The key constituents of the program comprise a tick box list of altogether 36 chemicals, a short questionnaire, and a predefined sampling/transport chain. In 2016, this program was carried out after a major accident on one site. Samples were collected from firefighters, other company employees and external rescue forces. Exposure to benzene, toluene and polycyclic aromatic hydrocarbons (PAHs) was monitored using sensitive, specific and quality-controlled biomonitoring methods. Results: An additional exposure to benzene was found only in firefighters, with a maximum S-Phenylmercapturic Acid (SPMA) concentration of about 40 µg/g creatinine. Most results were in the range of the general background, but moderately increased into the typical range of smokers. Benzene exposure was not only confirmed for active firefighters but also for post-accident firewatch forces. Biomarkers for toluene and PAHs were all within the normal range, which was unexpected since PAH biomarkers are often found in post-operation samples of firefighters. However, this result accords with the observation of an almost vertical smoke propagation. Conclusion: A high degree of preparedness is essential for the conduction of HBM programs after chemical incidents. Professional firefighters are usually well prepared to avoid overexposure to chemicals. However, residual spot contamination can be relevant and needs to be considered for professional safety measures.